2017
DOI: 10.1534/genetics.117.300057
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Gene Conversion Tracts Associated with Repair of a Defined Double-Strand Break in Saccharomyces cerevisiae

Abstract: Mitotic recombination between homologous chromosomes leads to the uncovering of recessive alleles through loss of heterozygosity. In the current study, a defined double-strand break was used to initiate reciprocal loss of heterozygosity between diverged homologs of chromosome IV in These events resulted from the repair of two broken chromatids, one of which was repaired as a crossover and the other as a noncrossover. Associated gene conversion tracts resulting from the donor-directed repair of mismatches forme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Though the length of homology on each side of the induced DSB was similar in the two systems (~2 kb), the median length of CO-associated hetDNA was ~1.9 kb, while that associated with SDSA events was only ~1.1 kb (p = 0.0002). The significant hetDNA length difference between COs and NCOs in similar ectopic systems, but not in allelic systems [ 43 , 45 ], is consistent with our previous suggestion that the second-end engagement, which is a prerequisite for reciprocal CO formation in the canonical DSB repair pathway, requires more extensive homology length than does SDSA [ 36 , 53 ]. We suggested that the D-loop size and stability is directly related to the length of hetDNA that forms during the initial strand invasion, which may be limited by substrate size in ectopic assays.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Though the length of homology on each side of the induced DSB was similar in the two systems (~2 kb), the median length of CO-associated hetDNA was ~1.9 kb, while that associated with SDSA events was only ~1.1 kb (p = 0.0002). The significant hetDNA length difference between COs and NCOs in similar ectopic systems, but not in allelic systems [ 43 , 45 ], is consistent with our previous suggestion that the second-end engagement, which is a prerequisite for reciprocal CO formation in the canonical DSB repair pathway, requires more extensive homology length than does SDSA [ 36 , 53 ]. We suggested that the D-loop size and stability is directly related to the length of hetDNA that forms during the initial strand invasion, which may be limited by substrate size in ectopic assays.…”
Section: Discussionsupporting
confidence: 87%
“…A similar event in MMR-proficient cells would give rise to a single gene conversion tract located on only one side of the DSB. We previously reported frequent DSB-initiated allelic CO events with just a single gene conversion tract and attributed these to frequent restoration-type repair [ 43 ]. Because D-loop migration erases the hetDNA created by strand invasion, however, this may have contributed to the one-sided gene conversion tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more than one mismatch machinery may have been involved in repairing breaks. Strikingly, similar LOH signatures were observed during mitotic DSB repair in S. cerevisiae (Guo et al 2017;Hum and Jinks-Robertson 2017), suggesting that these mechanisms may have been conserved through evolution.…”
Section: Discussionmentioning
confidence: 59%
“…There are two plausible interpretations of the observation of the results shown in Figure 7A: oxidative damage during aerobic growth is responsible for about half of spontaneous recombination events, or recombinogenic lesions are less efficiently repaired in cells grown anaerobically. To distinguish between these possibilities, we examined the efficiency of repair of a DSB induced in a strain (SJR4317) with the galactose-inducible gene encoding the mega-endonuclease I-SceI (40) under aerobic and anaerobic conditions. This diploid is closely related to JSC25-1 described above, and contains the heterozygous SUP4-o marker near the end of the right arm of IV.…”
Section: Resultsmentioning
confidence: 99%